Depressive symptoms are associated with worsened severity of the metabolic syndrome in African American women independent of lifestyle factors: A consideration of mechanistic links from the Jackson heart study. (June 2016) - Gurka, Matthew J.; Vishnu, Abhishek; Okereke, Olivia I.; Musani, Solomon; Sims, Mario; DeBoer, Mark D.
Highlights: Among women depressive symptoms correlated with metabolic syndrome (MetS) severity. Depressive symptoms and MetS severity were related to less physical activity. Depressive symptoms and MetS severity were also related to higher levels of hsCRP. The degree of depressive symptoms did not relate to the rate of MetS worsening. Abstract: Background: Depression and the metabolic syndrome (MetS) are both risk factors for cardiovascular disease and type 2 diabetes mellitus. Prior studies in predominantly White populations demonstrated that individuals with depressive symptoms at baseline are more likely to develop future MetS. We tested the hypothesis that depressive symptoms would contribute to a more pronounced increase in MetS severity among African Americans in the Jackson Heart Study (JHS). Methods: We used repeated-measures modeling among 1743 JHS participants during Visits 1–3 over 8 years of follow-up to evaluate relations between depressive symptom score (Center for Epidemiologic Survey-Depression (CES-D)) at baseline and a sex- and race/ethnicity-specific MetS severity Z-score at each visit. Results: 20.3% of participants had a CES-D score ≥16, consistent with clinically-relevant depressive symptoms. Higher depressive-symptom scores were associated with higher MetS severity in women but not men (p = 0.005 vs. p = 0.490). There was no difference by depressive symptom score with rate of change in MetS severity over time. Both depressive-symptom score and MetS severity Z-score were associated with lower levels of physical activity and higher levels of C-reactive protein; however, addition of these to the regression model did not attenuate the association between depressive symptoms and MetS severity. Conclusion: African American women but not men in the JHS exhibit relationships between baseline depressive symptoms and MetS severity over an 8-year period. These data may have implications for targeting of MetS-associated lifestyle changes among individuals with depressive symptoms.